2016
DOI: 10.4172/2167-1095.1000223
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hypersplenism Causes of Peripheral Cytopenias in Patients with Cirrhotic Portal Hypertension: A Review

Abstract: Hypersplenism and non-hypersplenism factors, either alone or in combination, can cause peripheral cytopenias in patients with cirrhotic portal hypertension. Although non-hypersplenism factors account for only a small proportion of patients, they do exist. When peripheral cytopenias do not improve, or fail to improve adquately, or even become worse after splenectomy in these patients, non-hypersplenism factors should be considered. This review aims to provide an overview of non-hypersplenism factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…In 15.9% (62/390) of patient-times with peripheral cytopenia, the blood cells counts increased but they did not reach normal, indicating that in addition to hypersplenism other factors were involved. 23 Also, thrombocytopenia is related to thrombopoietin (TPO), and the more severe the liver cirrhosis, the worse the liver functional reserve, thus the more obvious the thrombocytopenia, and the poorer the prognosis. 35 TPO is almost specially produced by liver cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 15.9% (62/390) of patient-times with peripheral cytopenia, the blood cells counts increased but they did not reach normal, indicating that in addition to hypersplenism other factors were involved. 23 Also, thrombocytopenia is related to thrombopoietin (TPO), and the more severe the liver cirrhosis, the worse the liver functional reserve, thus the more obvious the thrombocytopenia, and the poorer the prognosis. 35 TPO is almost specially produced by liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, according to Kalambokis and Tsianos, this etiology has not been well documented. 8 Many scholars have now reported that toxicity of hepatitis virus to bone marrow, [9][10][11] liver hypofunction, 12,13 gastrointestinal bleeding, 14 immune dysfunction, 15,16 drug toxicity, [17][18][19] peripheral platelet destruction, 20 hematopoietic disorders caused by vitamin and nutritional deficiency [21][22][23] and at the same time with the blood system diseases can also lead to peripheral cytopenia. Karasu and Tekin 24 stated that hypersplenism cannot be the only cause for patients with peripheral thrombopenia.…”
Section: Introductionmentioning
confidence: 99%
“…The blood picture (hemogram) and blood film were done for all the 296 patients. Haematologically, hypersplenism was defined as leukocyte count of <4.0×109/L, an erythrocyte count of <4.0×1012/L, and/or a platelet count of <150×109/L [8]. The prevalence and pattern of hypersplenism were assessed.…”
Section: Assessment Of the Presence And Severity Of Hypersplenismmentioning
confidence: 99%
“…Depending mainly on the severity, cytopenia, was graded as mild, moderate, or severe, and given a total score of <2 points, 2-3 points, and >3 points, respectively. PLTs count of 50-100×109/L was scored as 1, 30-50×109/L as 2, and <30×109/L as 3; a RBCs count of 3-4×1012/L was scored as 0, and <3×1012/L as 1; a WBC count of 2-4×109/L was scored as 0, and <2×109/L as 1 [8]. Presence of hypersplenism in patients with cirrhosis and PHT, was assessed in comparison with those who did not develop hypersplenism, and comparison between different grades of hypersplenism was also done, as regards to Child-Pugh score, MELD score, presence of HCC, PVT, ascites, portosystemic collaterals, portal haemodynamic and other clinical data.…”
Section: Assessment Of the Presence And Severity Of Hypersplenismmentioning
confidence: 99%